The Profession of Driver Tractor in Gender Equality Program through Jungle Queen (Study on Female Drivers in PT. Harapan Sawit Lestari in Manis Village of Manis District of Ketapang Regency, West Kalimantan) - Amin, Syahroli; Vina Salviana Darvina Soedarwo; Muhammad Hayat; Tutik Sulistyowati; Luluk Kumalasari (Jurnal Perempuan dan Anak, 2023)
This research was conducted at PT. Harapan Sawit Lestari is a division of Manis Mata Estate with the aim of research to find out the tractor driver profession in the gender equality program through the jungle queen. The approach in this study uses a qualitative descriptive type of research. The results showed that female tractor drivers at PT. Harapan Sawit Lestari started in 2006 until now, one of which is in the Manis Mata Estate division with a percentage of 38% being women in terms of treatment and rights between men and women are the same as employees, the difference is in maternity leave for women. The dual role of women as tracker drivers is in the form of domestic roles and public roles. One form of the company's commitment to the sustainability of the gender equality program is through a program, one of which is through the Cargill Women's Network (CWN) which is to be achieved by 2030 while supporting the Sustainable Development Goals (SDGs) program. Through Jungle Queen committee PT. Harapan Sawit Lestari as a subsidiary of Cargill implements a gender equality program to develop women in an industry. The factors that influence women's work are the economy, self-interest, family future, and support from their husbands. The impact of women has a dual role in being tired and bored, as well as the obstacles faced in the form of having toddlers, bad weather, lack of communication networks in the field. The feeling felt as an employee is a feeling of pride, a feeling of pleasure, feeling that work equipment is fulfilled. The response from colleagues in the sweet eye estate environment towards women and work as female tractor drivers received a positive response.